Sentiment Analysis of Students’ Perception towards the Implementation of Limited In-Person Learning: A Post-Pandemic Perspective - Cahapin, Erwin L.; Santiago, Cereneo Jr Sailog; Malabag, Beverly A.; Reyes, Jocelyn L.; Legaspi, Gemma S.; Benedicto, Marion Joyce (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This article is the second in a series on the opinions of students (also referred to as respondents). The preceding article in this series concentrated on sentiment analysis of students' online learning experiences. In this paper, the students' opinions about their learning condition and thoughts or feelings toward the implementation of limited in-person or face-to-face learning were investigated. Method – The sentiment analysis was utilized in the study particularly in obtaining the polarity, subjectivity, and presentation of visualization results.  A total of 459 respondents answered the two open-ended questions where obtained 918 unstructured responses. A total of 27,316 words underwent data cleaning and data pre-processing. Text classification using sentiment analysis was performed. Results – The result revealed that the respondents’ learning condition is combined with positive, negative, and neutral sentiments. The opinions to implement limited in-person learning were dominated by positive thoughts. Students’ thoughts on the implementation of limited face-to-face learning were expressed based on their learning conditions, experiences, and expectations. Conclusion – Undoubtedly, the COVID-19 pandemic has challenged students' financial, social, and mental well-being. They have to deal with the major issues brought on by educational system disruptions, which decreased their interest and enthusiasm in learning. The learners' concern about returning to school was expressed as both positive and negative. Their negative views indicate valuing what is more important during a health crisis just like the Covid-19 pandemic. Recommendations – Educators need capability pieces of training where approaches and instructional methodologies are emphasized in the course syllabi which take health precautions into account for learners both in the face-to-face and online modality. Research Implications – The overall sentiments provided insights to administrators and educators of the learning institutions to re-think and make sound decisions in the execution of their plans in welcoming back the learners successfully.